Are there characteristic motion patterns in the lumbar spine during flexion?. (21st March 2018) - Zander, Thomas; Bashkuev, Maxim; Schmidt, Hendrik
Abstract: Flexion is the main motion of the lumbar spine. While in vitro tests with pure moments suggest larger intra-segmental rotations for the more caudal segments, in vivo results show diverging motion distributions. The present study analysed the motion distribution in vivo of 320 asymptomatic subjects. The change of the back curvature between standing and upper body flexion was determined using a non-invasive measurement device. Linear, bilinear, trilinear, quadratic, and cubic regression models were fitted to the segmental motion distribution over the lengths of the lordosis to categorise characteristic motion patterns. Simplicity and approximation quality were used to assign the motion distributions to the regression models. Seventy-seven percent of the motion distributions could be explained by a bilinear model. A further 12% and 11% could be represented by a trilinear and linear model, respectively. Less than 1% of the distributions could not satisfactorily be represented by the models. All of the bilinear models displayed maximum flexion in approximately the middle of lordosis. All linear models showed a decreasing rotation from caudal to cranial. Most of the trilinear models displayed a distribution similar to the bilinear. Age, sex, body height, and weight did not significantly affect these distributions. This in vivo study identified characteristic motion patterns in the lumbar spine during flexion. The quantitative results provide a clear description of the healthy condition and may serve to identify spinal motion abnormalities.